2020
DOI: 10.1001/jama.2019.21411
|View full text |Cite
|
Sign up to set email alerts
|

Malpractice Liability and Health Care Quality

Abstract: IMPORTANCEThe tort liability system is intended to serve 3 functions: compensate patients who sustain injury from negligence, provide corrective justice, and deter negligence. Deterrence, in theory, occurs because clinicians know that they may experience adverse consequences if they negligently injure patients. OBJECTIVE To review empirical findings regarding the association between malpractice liability risk (ie, the extent to which clinicians face the threat of being sued and having to pay damages) and healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 55 publications
1
56
0
Order By: Relevance
“…Future research directions in softening the concrete and redeveloping the Standard of Care and nurses’ accountability according to the flow of practice changes could be considered [ 54 ]. Furthermore, while a recent systematic review suggested no association between greater risk of malpractice liability and health care quality [ 58 ], the emphasis is on engaging in physicians’ voice rather than the nurses’ voice [ 59 ]. While the delayed nursing care and missed care remain prominent in acute care hospitals internationally [ 60 , 61 ], nursing outlier patients can be a potential stressor worsening the current situation.…”
Section: Discussionmentioning
confidence: 99%
“…Future research directions in softening the concrete and redeveloping the Standard of Care and nurses’ accountability according to the flow of practice changes could be considered [ 54 ]. Furthermore, while a recent systematic review suggested no association between greater risk of malpractice liability and health care quality [ 58 ], the emphasis is on engaging in physicians’ voice rather than the nurses’ voice [ 59 ]. While the delayed nursing care and missed care remain prominent in acute care hospitals internationally [ 60 , 61 ], nursing outlier patients can be a potential stressor worsening the current situation.…”
Section: Discussionmentioning
confidence: 99%
“…Some states have have taken additional steps to provide protection to physicians who have shifted their practices to telemedicine and those whose treatment decisions may have been based on government directives. Earlier research has pointed to the impacts of medical malpractice pressures on physician treatment decisions (Frakes and Gruber (2019) and Mello et al (2020)). It is therefore plausible that states that added these liability waivers may have higher rates of physician compliance with the directives related to the postponement of elective and nonurgent care.…”
Section: State Policy Datamentioning
confidence: 99%
“…The compensation systems in Denmark and New Zealand are in contrast to the American system where both tort and compensation systems are incorporated as one. The American medical liability system is intended to serve three functions: compensate patients injured by negligence, promote corrective justice by providing a mechanism to rectify wrongful losses caused by defendants, and deter negligence (25). This adversarial litigation process can -in our opinion -destroy physicianpatient relationships and involves considerable emotional strain for both plaintiffs and defendants.…”
Section: Of 15mentioning
confidence: 99%